2017
DOI: 10.1111/liv.13328
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcomes of primary sclerosing cholangitis with and without inflammatory bowel disease in an Australian cohort

Abstract: Australian PSC patients have similar characteristics compared to European and North American cohorts. IBD is a significant predictor of gastrointestinal malignancies. Deaths were more common in PSC-IBD but overall transplant-free survival remained similar in PSC-IBD and PSC-only groups. An elevated INR was an independent predictor of death or liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
1
20
2
Order By: Relevance
“…First, although being a large academic liver centre, our hospital does not include a liver transplantation service, and as such may not be referred patients with more severe, end‐stage disease. Only one (3%) patient in our series underwent a liver transplantation (in another hospital), compared to 8–40% in other studies and this may overestimate the survival rate. Additionally, the median follow‐up time in our study was 5.5 years, which is at the lower end of the 5.2–9.6 years reported in other studies .…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…First, although being a large academic liver centre, our hospital does not include a liver transplantation service, and as such may not be referred patients with more severe, end‐stage disease. Only one (3%) patient in our series underwent a liver transplantation (in another hospital), compared to 8–40% in other studies and this may overestimate the survival rate. Additionally, the median follow‐up time in our study was 5.5 years, which is at the lower end of the 5.2–9.6 years reported in other studies .…”
Section: Discussioncontrasting
confidence: 72%
“…Only one (3%) patient in our series underwent a liver transplantation (in another hospital), compared to 8–40% in other studies and this may overestimate the survival rate. Additionally, the median follow‐up time in our study was 5.5 years, which is at the lower end of the 5.2–9.6 years reported in other studies . Still, only four (10%) patients were lost to follow up, meaning that complications were captured in most patients during the study period.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Moreover, geographic variations may exist in the PSC-IBD phenotype. In particular, studies from Oceania have noted patients with PSC-IBD to be at an increased risk of death and increased risk of gastrointestinal or hepatobiliary malignancies than patients with PSC alone[ 45 , 46 ]. In contrast, multiple studies from Asia have not identified significant differences in these outcome measures between patients with PSC-IBD and PSC alone[ 16 , 17 ].…”
Section: Primary Sclerosing Cholangitis and Inflammatory Bowel Diseasmentioning
confidence: 99%